Empowerment of Social Entrepreneurs for Women groups in Cultural Tourism Villages - Gesta Lionanda (International Journal of Social Service and Research, 2023)
Social entrepreneurship can be a solution for community empowerment, especially groups of women in remote villages who still live with the stigma that women do not have the same rights as men, especially in economic development and social empowerment, but this village has great natural and cultural tourism potential. This study aims to decipher, explain and analyze the empowerment of women's groups as social entrepreneurs in Cultural Tourism Villages. The research was conducted using a qualitative approach method where the techniques carried out to obtain data were through In-Depth Interviews, observations and documentation. From this research shows that women's groups can have the same opportunities and capacities as men in family and rural economic development to regions, especially handicraft industries, namely woven crafts, Sasirangan Batik and Bark which developed in line with the inauguration of Liyu Village as a cultural tourism village to the implementation of annual events in the form of Mesiwah Pare Gumboh and Melatu Wini. Then the development of natural potential that is still very natural and interesting, all efforts made through social enterprises create valuable social contributions for the Dayak Deah Community community in the remote Liyu Village.